High Entropy Alloys: Criteria for Stable Structure - Tripathy S.; Gupta G.; Chowdhury S.G. (My University, 2025)
An effort has been made to reassess the phase predicting capability of various thermodynamic and topological parameters across a wide range of HEA systems. These parameters are valence electron concentration, atomic mismatch (δ), electronegativity difference (Δχ), mixing entropy (ΔSmix), entropy of fusion (ΔSf), and mismatch entropy (Sσ). In continuation of that, two new parameters (a) Modified Darken–Gurry parameter (A = S) and (b) Modified Mismatch Entropy parameter (B = δ*Sσ) have been designed to predict the stable crystal structure that would form in the HEA systems considered for assessment. © 2017, The Minerals, Metals & Materials Society and ASM International.